Jamu the ancient Indonesian art of herbal healing - Beers, Susan-Jane (Periplus, 2001)
Just as India has Ayurveda and China has its traditional medicinal system, Indonesia has jamu: an integrated system of inner and outer health and beauty. Indonesian jamu has a 1,200-year-old history but is virtually unknown outside of that country. Now, an experienced writer has devoted herself to understanding jamu: its history, its applications and its potential for use outside its native environment. Author Susan-Jane Beers first encountered jamu after pain-killers failed to relieve her joint pain. A prescription from an expert made the pain go away. Now, in Jamu, she chronicles the practice of this holistic system, the materials and ingredients it employs and its rich background dating back to the ancient Javanese palaces where it was perfected. Complemented by over 100 photo-graphs, Jamu is the first definitive reference to this exotic yet practical health-care system.